Exploring the pathogenesis of insomnia and acupuncture intervention strategies based on the microbiota-gut-brain axis - Guo, Jia; Guo, Jixing; Rao, Xiang; Zhang, Rongni; Li, Qiang; Zhang, Kun; Ma, Shanbo; Zhao, Jingyu; Ji, Changchun (Frontiers in Microbiology, 2024)
Insomnia is a common sleep disorder observed in clinical settings, with a globally rising prevalence rate. It not only impairs sleep quality and daytime functioning but also contributes to a range of physiological and psychological conditions, often co-occurring with somatic and mental disorders. Currently, the pathophysiology of this condition is not fully understood. Treatment primarily involves symptomatic management with benzodiazepine receptor agonists, melatonin and its receptor agonists, sedative antidepressants, atypical antipsychotics, and orexin receptor antagonists. However, due to the adverse side effects of these drugs, including dependency, addiction, and tolerance, there is an urgent need for safer, more effective, and environmentally friendly treatment methods. In recent years, research on the microbiota-gut-brain axis has received significant attention and is expected to be key in uncovering the pathogenesis of insomnia. Acupuncture stimulates acupoints, activating the body's intrinsic regulatory abilities and exerting multi-pathway, multi-target regulatory effects. A substantial body of evidence-based research indicates that acupuncture is effective in treating insomnia. However, the unclear mechanisms of its action have limited its further clinical application in insomnia treatment. Therefore, this study aims to elucidate the pathogenesis of insomnia from the perspective of the microbiota-gut-brain axis by examining metabolic, neuro-endocrine, autonomic nervous, and immune pathways. Additionally, this study discusses the comprehensive application of acupuncture in treating insomnia, aiming to provide new strategies for its treatment.